THE METHODOLOGY OF TEACHING FINE ARTS - Ergasheva Orifakhon (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the role of fine art today and information about fine art and its essence, types and genres. In fact There are many types of art. They are fiction, music, visual arts, theater, cinema, there are other types of art, such as choreography, architecture, applied decoration. Usually, real existence is represented in visual images, forms, spatial dimensions or art that reflects on a plane (on the surface of paper) is called fine art. Descriptive the concept of art has a wide meaning. The artist was creating in visual arts he does not know the types and genres of this direction and becomes a real creator of fine art is a sign that he can’t.